Implementation of Denpasar Mayor’s Regulation Number 15 of 2020 on the Return BPHTB by Badan Pendapatan Daerah due to Cancellation of Sale and Purchase Agreement - Putu Ayu Sriasih Wesna; I Kadek Wahyu Fajar Sutoya; Luh Made Mahendrawati (Warmadewa Press, 2022)
In the case of a land sale and purchase agreement carried out by both parties, it often creates problems when the agreement is canceled, in this case it is canceled or null and void because of the unfulfilled conditions of the validity of an agreement so that BPHTB that has been paid as a result of the agreement will be submitted for cancellation by the parties or intermediaries, in this case a notary. The research method used is empirical legal research. The analysis used is descriptive analysis, namely the data that has been collected is processed to formulate the research conclusions. Then the research data were analyzed in depth. Based on the results of the research that the legal consequence of the cancellation of the sale and purchase agreement against the BPHTB that has been paid is that it can be returned but must include a valid cancellation deed from a notary, this is used to be taken into consideration as the basis for returning the BPHTB that has been paid Then the BPHTB that has been paid will be returned. Then the basis for considering the return of BPHTB by the Denpasar City Regional Revenue Agency against the cancellation of the land sale and purchase agreement is the completeness of the documents attached to the application in accordance with the Mayor of Denpasar City No. 13 of 2020 as strong evidence that the agreement is legally accompanied by the reasons that have been in the cancellation of the sale and purchase agreement.